Community-Based Legal Model for Narcotics Prevention: Protecting Children's Best Interests in Indonesia - Kaimudin, Arfan (Faculty of Law, University of Merdeka Malang, 2025)
The escalating prevalence of narcotics abuse among children in Indonesia exposes a fundamental legal protection deficit: the structural disjunction between the enforcement-centered orientation of Law Number 35 of 2009 on Narcotics and the protective obligations imposed by Law Number 35 of 2014 on Child Protection and the Convention on the Rights of the Child. Existing legal responses remain predominantly reactive, engaging children only after narcotics exposure has occurred, while the proactive normative architecture necessary for genuine prevention remains underdeveloped. This research employs a normative juridical methodology with statute and comparative approaches to address two questions: how should a community-based approach be legally positioned as a model for narcotics prevention among children under Indonesian positive law, and what is its ideal normative form in accordance with the best interests of the child principle. The analysis demonstrates that the community-based approach constitutes a constitutionally mandated preventive legal model, grounded in Article 104 of the Narcotics Law, Article 59(2)(e) of the Child Protection Law, and Article 28B(2) of the 1945 Constitution. Its ideal normative form integrates seven components: structured community participation, legal education and awareness, family resilience programs, child-friendly environmental infrastructure, cross-sector institutional collaboration, program sustainability and accountability, and restorative justice as the primary remedial response. Legislative reform is recommended to operationalize this model as a binding and durable legal framework for child protection.